Green Supply Chain Management Practices and Effects on Organizational Performance in Zambian Beverage Manufacturing Industry - Ethel Tembo Mwanaumo; Bupe Mutono Mwanza; Levy Siaminwe (Logistic and Operation Management Research (LOMR), 2023)
Organizational performance is important because it directly impacts the overall success and sustainability of a business. This study aims to investigate the effects of Green Supply Chain Management (GSCM) practices on organizational performance in the Zambian beverage industry, using an embedded mixed methods model. Quantitative data was collected using a questionnaire from 32 participants out of 37 and analyzed using descriptive and inferential statistics using STATA Version 14.2. Qualitative data was collected from in-depth interviews with 9 Supply Chain Specialist and Industry Experts, selected based on availability, convenience and volunteering. The results show that Green Purchasing, Green Manufacturing, Green Distribution/Marketing, and Reverse Logistics each had a positive influence on organizational performance. Internal drivers had a significant and positive effect on organizational performance, while external barriers had a negative influence. Stepwise regression revealed that 14.9% of the variations in organizational performance were explained by the model, with internal drivers being the most significant factor. The study concludes that major benefits of applying GSCM practices are reduced production costs, good reputation with the municipalities and law enforcers, and long-term savings due to efficiency in production. The study recommends that companies should increase their knowledge of GSCM practices and engage in more sustainable practices to reduce production costs and prevent further environmental degradation. Future studies could include research in factors that can improve GSCM practices in the Zambian beverage manufacturing sector.